SATISFACTION INDICATORS OF ATHLETES WITH DAMAGE OF THE LOCOMOTOR APPARATUS WITH THE ORGANIZATION OF COMPETITIONS IN CYBATTLE - Kornev, A.V.; Shvetsov, A.V.; Pravdov, D.M.; Ereshko, N.E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the degree of satisfaction of athletes with lesions of the musculoskeletal system with the organization of competitions in cybatletics. Methods and structure of the study. To achieve the goal of the study, a survey was conducted of athletes with lesions of the musculoskeletal system as part of open competitions in cybatletics, which took place from March to May 2021 on the basis of the Russian State Social University. The survey involved 80 people (58 men and 22 women). Athletes had to answer questions in which they assessed their attitude to holding and organizing kibatletics competitions on a 10-point scale. Results and conclusions. A survey of athletes who took part in kibatletics competitions made it possible to identify the degree of satisfaction with the organization and conduct of the competitions. The degree of satisfaction was studied according to the following parameters: the general level of organization and holding of competitions in cybatletics; competition schedule; favorable atmosphere during familiarization with the track and the competition; catering; the quality of work of the refereeing team and volunteers.